Assessment of the application level of radiation protection and awareness of radiation safety regulations among the radiographers at Yogyakarta Special Region, Indonesia - Ahmad Rafiq Mohammad Abu Arrah Arif Faisal Ahmad Hamim Sadewa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
A strong relation between cancers and radiation exposure has been reported. Radiation may damage DNA in thecell. Therefore, radiation protection program must be applied in the radiology department. Morover, the radiographershould have high level of awareness and risk assessment for radiation. Personal radiation monitoring is one of themain radiation protection, especially for pregnant worker and her fetus. This study was conducted to evaluate theapplication, awareness and risk assessment levels of radiation protection among radiographers at hospitals inYogyakarta Special Region, Indonesia. This was a descriptive study, applying a cross sectional survey at hospitals inYogyakarta. The subjects were radiographers of both governmental and private hospitals. There were 101 respondentsfrom a total of 124 radiographers. The data obtained were tabulated and analyzed using Chi Square test. The studyrevealed that 69.3% of the respondents had low application level of radiation protection, 19.8% did not know themeaning of ALARA (As Low As Reasonably Achievable), 50.5% were not aware of Inverse Square Law. The studyalso reported that 36.6% of the respondents did not know the amount of radiation that entered their body last year,61.4% of radiographers thought that the risk assessment of radiation was not enough, 18.8% of radiographerswere never use any radiation monitoring device, and 90.1% stated that there was no additional protection orradiation monitoring to the pregnant radiographer. However, there were no significant differences between durationof working, type of imaging modality, academic level, and training course for radiation protection. In conclusion,there was no difference in the application, awareness, and risk assessment levels of radiation protection among theradiographers at hospital in Yogyakarta Special Region between duration of working, type of medical imaging modality,academic level, and training on radiation protection. In addition, the application, awareness, and risk assessmentlevels of radiation protection were not sufficient.Key words: radiation protection – ALARA – radiographer – hospital – risk assessment